2021
DOI: 10.1111/jgs.17013
|View full text |Cite
|
Sign up to set email alerts
|

Antidopaminergic‐Antiparkinsonian Medication Prescribing Cascade in Persons with Alzheimer's Disease

Abstract: OBJECTIVES: Persons living with Alzheimer's disease (AD) may be at increased risk for prescribing cascades due to greater multimorbidity, polypharmacy, and the need for more complex care. Our objective was to assess the proportion of the antidopaminergic-antiparkinsonian medication prescribing cascades among persons living with Alzheimer's disease. SETTING: Two large administrative claims databases in the United States. PARTICIPANTS: We identified patients aged ≥50 on January 1, 2017, who were dispensed a drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
(48 reference statements)
0
13
0
2
Order By: Relevance
“…Most studies ( n = 88) were retrospective cohort studies, 5 , 7 , 18 , 21 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsunclassified
See 2 more Smart Citations
“…Most studies ( n = 88) were retrospective cohort studies, 5 , 7 , 18 , 21 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsunclassified
“… 24 , 26 , 30 , 41 , 44 , 50 , 53 , 74 , 117 and parkinsonism ( n = 9). 27 , 29 , 30 , 31 , 46 , 57 , 63 , 82 , 119 …”
Section: Resultsunclassified
See 1 more Smart Citation
“…107 The suspected ADRs, symptoms or new diagnoses explored were broad-ranging (see Table 2) most commonly depression (n=13) 33,37,40,45,52,55,57,73,95,99,100,112,114 ; peripheral oedema (n=11) [5][6][7]28,36,64,81,98,[105][106][107]118 ; urinary incontinence (n=9). 24,26,41,44,50,53,75,81,119 and parkinsonism (n=9) 27,29,31,46,57,81,84,123,124…”
Section: Suspected Adverse Reaction(s)mentioning
confidence: 99%
“…91,93,103 No association between drug pairs could be determined for several studies, largely due to either a crosssectional study design examining concurrent drug use, insufficient drug-pair sample size to determine a sequence ratio or reporting of incidence rates with no incidence rate ratio (labelled N/A in Figure 2). 6,21,25,43,46,53,55,64,81,114,116,117,123,125,126 Several studies reported at least one negative association between drug pairs, indicating a reduced likelihood of the second medication being initiated (see eTable 3 Supplementary materials). 33,60,[68][69][70]75,83,89,91,95,113 Modifiers of identified associations Older people (aged [?…”
Section: New Medication(s) Prescribedmentioning
confidence: 99%